2013
DOI: 10.1029/2012jb009721
|View full text |Cite
|
Sign up to set email alerts
|

Global observation of vertical‐CLVD earthquakes at active volcanoes

Abstract: [1] Some of the largest and most anomalous volcanic earthquakes have non-double-couple focal mechanisms. Here, we investigate the link between volcanic unrest and the occurrence of non-double-couple earthquakes with dominant vertical tension or pressure axes, known as vertical compensated-linear-vector-dipole (vertical-CLVD) earthquakes. We determine focal mechanisms for 313 target earthquakes from the standard and surface wave catalogs of the Global Centroid Moment Tensor Project and identify 86 shallow 4.3 ≤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 185 publications
(309 reference statements)
3
51
1
Order By: Relevance
“…The interpretation that the 2009 earthquakes were caused by magmatic intrusion centered on or near the volcano is also consistent with the fact that at least one of the earthquakes had a highly non-double-couple focal mechanism (Shuler et al, 2010) (Fig. 3A), similar to some earthquakes documented at other active volcanoes (Ekström, 1994;Shuler and Ekström, 2009).…”
Section: Pre-eruption Earthquake Swarmsupporting
confidence: 81%
“…The interpretation that the 2009 earthquakes were caused by magmatic intrusion centered on or near the volcano is also consistent with the fact that at least one of the earthquakes had a highly non-double-couple focal mechanism (Shuler et al, 2010) (Fig. 3A), similar to some earthquakes documented at other active volcanoes (Ekström, 1994;Shuler and Ekström, 2009).…”
Section: Pre-eruption Earthquake Swarmsupporting
confidence: 81%
“…It has been shown that certain processes in volcanic regions, such as magmatic and hydrothermal fluid migration, may be accompanied by earthquakes with significant non-DC components (Shuler et al, 2013). However, results obtained in this work indicate the seismological observations both at local and regional distances can be well reproduced by a pure DC model for a shear failure on a planar fault.…”
Section: Discussioncontrasting
confidence: 50%
“…Shuler et al . [] found a strong correlation between the occurrence of vertical‐CLVD mechanisms and volcanic unrest, where vertical‐P mechanisms generally occur after eruptions. The location and timing of event O5 and vPC1 might therefore be indicative for volcanic processes such as deflating or collapse of a magma chamber in the center of segment C during the swarm.…”
Section: Discussionmentioning
confidence: 99%